The comparative analyses of reduced graphene oxide (RGO) prepared via green, mild and chemical approaches - Faniyi, I. O.; Fasakin, O.; Olofinjana, B.; Adekunle, A. S.; Oluwasusi, T. V.; Eleruja, M. A.; Ajayi, E. O. B. (SN applied sciences, 2019)
In this work, the reducing power of three reductants: hydrazine (chemical), ascorbic acid (mild) and the extract of Amaranthus hybridus (green) were investigated. Graphene oxide (GO) was synthesized by modified Hummer’s method and was reduced by hydrazine (RGO-HZ), ascorbic acid (RGO-AA) and the extract of Amaranthus hybridus (RGO- AH ). GO, RGO-HZ, RGO-AA and RGO- AH were characterized using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy and ultraviolet visible spectrometry. The FTIR spectra showed the presence of oxygen functionality groups in GO which were reduced in all RGOs. The morphological properties showed that RGOs sheets were exfoliated forming clusters with roughened surfaces while the optical energy band gaps of 2.19, 3.90, 3.60, and 3.20 eV were estimated for GO, RGO-HZ, RGO-AA and RGO- AH respectively. It can be concluded that the three reductants demonstrated good reducing capacities. The ascorbic acid and the extract of Amaranthus hybridus , apart from being environmentally friendly, can also be good substitutes for the dangerous chemical hydrazine.